Business Fashion: Masculinity, Class and Dress in 1870s Australia. Issue 2 (3rd April 2017) - Bellanta, Melissa
Abstract : This article explores the emergence of 'business fashion' as a new mode of male dress in 1870s Australia. The focus is on men at the vanguard of this new fashion: namely, bankers and sharebrokers in New South Wales' gold-mining towns during a gold rush between 1871 and 1874. The rise of business dress offers us insight into the surprising extent of male interest in fashion in late-colonial Australia – and fresh perspectives on the history of Australian masculinity, class and consumption as a consequence. Abstract :